2019
DOI: 10.1021/acs.iecr.8b04142
|View full text |Cite
|
Sign up to set email alerts
|

System Level Exergy Assessment of Strategies Deployed for Solid Oxide Fuel Cell Stack Temperature Regulation and Thermal Gradient Reduction

Abstract: Several operational strategies for Solid Oxide Fuel Cell (SOFC) temperature regulation and temperature gradient minimization at cell scale have previously been assessed by the authors (Amiri et al., Ind. Eng. Chem. Res., 2016). The application of such strategies at system scale, however, requires a numerical linkage between the cell and system performance metrics allowing simultaneous evaluation of the dominant process interactions. The objective of this study is to analytically examine the effectiveness and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…10-20 %) in the SOFC operation. In previous works co-authors have quantitatively shown that the utilisation of oxygen-enriched air (OEA) can improve the SOFC's efficiency at cell [20] and system level [21] causing thermal behaviour concerns. The efficiency rise essentially occurs due to two reasons (i) the catalyst sites are more effectively occupied by reactants (ii) higher partial pressure of oxygen boosts the reversible OCV.…”
Section: Voltage Interruption Simulation Of Enriched Air Impactmentioning
confidence: 99%
See 1 more Smart Citation
“…10-20 %) in the SOFC operation. In previous works co-authors have quantitatively shown that the utilisation of oxygen-enriched air (OEA) can improve the SOFC's efficiency at cell [20] and system level [21] causing thermal behaviour concerns. The efficiency rise essentially occurs due to two reasons (i) the catalyst sites are more effectively occupied by reactants (ii) higher partial pressure of oxygen boosts the reversible OCV.…”
Section: Voltage Interruption Simulation Of Enriched Air Impactmentioning
confidence: 99%
“…Amiri et al, developed a model to simulate a planar SOFC at both the stack and the system scales [20] with a focus on the SOFC thermal management. Most of the models used for SOFC thermal management are steady-state models [21]. Whilst they are extremely useful for capturing internal hotspots and nonuniformities in the steady-state operation of SOFC, the thermal dynamics are not taken into account.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that anode gas recycling could be used strategically for managing the gradients within the stack, while also enhancing fuel utilisation and water management. The thermal management challenges and opportunities were further investigated in subsequent work [20,30] in which we sought further operation relevant strategies to improve the SOFC thermal homogeneity. This work resulted in novel opportunities such as enriched air utilisation and also combination of various approaches to achieve optimum results.…”
Section: Modeling and Simulation At The System Scalementioning
confidence: 99%
“…This analogy is attributed to the origin of biogas, i.e., by the biomass from which the biogas has been produced, while the operating conditions selected for the conversion of organic material to biogas are also important for the electricity produced [6]. In this context, several layouts of stand-alone power plants have been proposed, where a fuel cell is inevitably included [7][8][9]. In the present project, a thermodynamics-based model for the optimization of the operation of SOFC-based power plants is presented under specific assumptions (for details, see Section 2).…”
Section: Introductionmentioning
confidence: 99%